The Influence of Store Atmosphere on Gen Z Visit Intention - Almaz, Bimo; Suryawardani, Bethani (Manunggal Halim Jaya, 2026)
This study investigates the influence of store atmosphere on the visit intention of Generation Z consumers at String Café Bandung, a café known for its modern minimalist interior and social media–oriented ambiance. The research adopts a quantitative approach, using purposive sampling to gather responses from 120 Gen Z individuals who have visited or intend to visit the café. Data were collected through structured questionnaires and analyzed using simple linear regression via SPSS version 22. The findings indicate a strong positive relationship between store atmosphere and visit intention, with a correlation coefficient (R) of 0.871 and a coefficient of determination (R²) of 0.758. The t-test results (t = 19.224, sig. = 0.000) and ANOVA (F = 369.579, sig. = 0.000) confirm the significant effect of store atmosphere elements—including layout, lighting, visual aesthetics, and ambient cues—on Gen Z's behavioral intention to visit. This study reinforces the Theory of Planned Behavior by demonstrating how physical and sensory environmental stimuli shape psychological responses in digitally native consumers. The results provide practical insights for café operators and brand strategists seeking to design emotionally engaging and visually compelling environments that resonate with Gen Z expectations. Moreover, it highlights the need for cohesive alignment between a café's physical space and online representation, especially in markets where visual experience drives consumer decision-making.